Our iron roads their history, construction, and administration - Williams, Frederick Smeeton, 1829-1886 (Bemrose & Sons, 1883)
'Our Iron Roads' gives a detailed account of the early history of the railways in Britain and explains at length the construction of embankments, cuttings, tunnels and viaducts.